Lokale Kultur und die Neuerfindung der Hafenstadt - Warsewa, Günter (Raumforschung und Raumordnung | Spatial Research and Planning, 2010)
During the course of transformation of social and economic structures the typical port-city in the western, industrialized world underwent serious changes or deviations of its traditional development path. Nevertheless the changing patterns of local structures and the modernisation of the local institutional system reflect essential elements and expressions of a typical local culture. In this process the specific local culture of the port-city turns out to be a control mechanism as well as an efficient resource extrapolating the individual logic of the place. Consequently, the re-invention of the port-city does not only express a simple logic of adaptation to global dynamics. Instead, the re-invention of the port-city appears as an expression of a certain autonomy and “individuality” which reproduces common characteristics of the port-cities as well as their difference to the territorial, inland towns.